The broken table : the Detroit Newspaper Strike and the state of American labor - Rhomberg, Chris, 1959- (Russell Sage Foundation, 2012)
"In The Broken Table, Chris Rhomberg sees the Detroit strike as a historic collision of two opposing forces: a system in place since the New Deal governing disputes between labor and management and decades of increasingly aggressive corporate efforts to eliminate unions."--Jacket.